Integration Between Some Soil Improvers and Salt-Resistant Microbes to Improve Some Soil Properties and Their Productivity in Ras Suder, South Sinai, Egypt. - Mohamed Abou Youssef; Salah El-Cossy; Samah Abdel-Azez (New Valley Journal of Agricultural Science, 2023)
A field experiment was conducted on a sandy loam soil in Wadi Sudr South Sinai, Egypt, to study the effect of a mixture of potatoes waste (PW) and farm yard manure (FYM), using a combination for the mixture FYM and PW, with two levels of salt-resistant microbes (SRM) (0 and 7 L ha-1) to reflect some of the properties of calcareous soil below saline irrigation and to improve the sunflower yield. The data obtained showed that soil bulk density (BD), Penetration resistance (PR), Hydraulic conductivity (HC), pH, and CE decreased with increasing application rates of PW using two rates of SRM, while Maximum water holding capacity (MWHC) and Organic Carbon (OC) were increased. The data obtained showed that the yield of sunflower seeds increased with increasing application rates of PW using two rates of SRM. The average increases in sunflower seeds yield were 23.21, 27.68, 44.64, 59.82 and 75.00 % relative to control (0 FYM + 0 PW) Mg ha-1 with the application mix of FYM and PW without SRM in the same mixes, respectively. Although they achieved 29.82, 39.47, 55.26, 73.68 and 90.35%, respectively, for blends of FYM and PW with SRM additions on the same blend. High significance was found between the sunflower seed yield altered by FYM and PW mixing and pH, EC, OC, BD, PR, HC or MWHC, respectively. So, we can say that the application mix of FYM+PW is considered effective in improving calcareous soil properties and productivity, which reduces environmental pollution from these wastes.